PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KABUPATEN SAROLANGUN - , Rosnela Ginting; , Dr. Agus Pramusinto, MDA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Participation of community in process of local development planning set by the government through MUSRENBANG, in fact, has not resulted in ideal participation, the government has not been able to reduce its roles as âdoerâ and implement its governmental role properly, as âfacilitatorâ. It causes many policies created as if these were made through public consulting